Differential Bacteriophage Efficacy in Controlling Salmonella in Cattle Hide and Soil Models - Xie, Yicheng; Thompson, Tyler; O’Leary, Chandler; Crosby, Stephen; Nguyen, Quang X.; Liu, Mei; Gill, Jason J. (Frontiers in Microbiology, 2021)
Asymptomatic Salmonella carriage in beef cattle is a food safety concern and the beef feedlot environment and cattle hides are reservoirs of this pathogen. Bacteriophages present an attractive non-antibiotic strategy for control of Salmonella in beef. In this study, four diverse and genetically unrelated Salmonella phages, Sergei, Season12, Sw2, and Munch, were characterized and tested alone and in combination for their ability to control Salmonella in cattle hide and soil systems, which are relevant models for Salmonella control in beef production. Phage Sergei is a member of the genus Sashavirus, phage Season12 was identified as a member of the Chivirus genus, Sw2 was identified as a member of the T5-like Epseptimavirus genus, and Munch was found to be a novel “jumbo” myovirus. Observed pathogen reductions in the model systems ranged from 0.50 to 1.75 log10 CFU/cm2 in hides and from 0.53 to 1.38 log10 CFU/g in soil, with phages Sergei and Sw2 producing greater reductions (~1 log10 CFU/cm2 or CFU/g) than Season12 and Munch. These findings are in accordance with previous observations of phage virulence, suggesting the simple ability of a phage to form plaques on a bacterial strain is not a strong indicator of antimicrobial activity, but performance in liquid culture assays provides a better predictor. The antimicrobial efficacies of phage treatments were found to be phage-specific across model systems, implying that a phage capable of achieving bacterial reduction in one model is more likely to perform well in another. Phage combinations did not produce significantly greater efficacy than single phages even after 24 h in the soil model, and phage-insensitive colonies were not isolated from treated samples, suggesting that the emergence of phage resistance was not a major factor limiting efficacy in this system.